“Eco-caring together” pro-ecological group-based community interventions and mental wellbeing: a systematic scoping review - Baker, Kane; Chioran, Bianca; Marks, Elizabeth (Frontiers in Psychology, 2024)
Background Poor mental wellbeing is a challenge for societies across the world, as is the increasing threat of climate change, and emerging evidence suggests these challenges are interrelated. Green and social prescribing of non-clinical interventions hold promise as a cost-effective and widely accessible way to improve wellbeing, and interest is growing in whether pro-ecological communal activities have mutual benefits for both people and the planet. Objectives Communal pro-ecological activities are growing in popularity, and research is gathering pace into whether participation influences mental wellbeing. The present systematic review scopes the existing evidence base to explore what is being done, what is being found, and what additional research is required. Methods Electronic databases (PsychNET, PubMed, Scopus, and Web of Science) were searched for studies that involved groups of people undertaking pro-ecological activities, where components of mental wellbeing were assessed. Eligibility criteria were purposely broad, including all study designs and participants across the lifespan. Results Thirty-seven eligible studies were identified. Nearly half of the studies used mixed-method designs, and most studies used surveys or interviews to evaluate outcomes. Most pro-ecological activities involved planting vegetation, and habitat creation, maintenance, or restoration. Methodological quality varied considerably. Among the perceived therapeutic mechanisms reported, the social elements of the interventions were prominent. Discussion Coherent synthesis of the current evidence base is challenging given the heterogeneous range of methods, samples, and interventions within the studies. However, the results here demonstrate promise that with future research and better methodological rigor, pro-ecological group-based interventions hold the potential to improve mental wellbeing and influence sustainable behavior. Systematic review registration https://osf.io/vmpr6/.